Answer:
y = -1
Explanation:
to solve this equation, you would solve for y by isolating y on one side of the equation
5(2y - 1) = 3(y - 4) < distribute 5 into 2y - 1 and 3 into y - 4
5(2y - 1)
5 x 2y = 10y
5 x - 1 = -5
= 10y - 5
3(y - 4)
3 x y = 3y
3 x -4 = -12
= 3y - 12
we get the new equation:
10y - 5 = 3y - 12 < add 12 to both sides to eliminate -12 from the right side
+ 12 + 12
10y + 7 = 3y < subtract 10y from both sides
-10y -10y
7 = -7y < divide both sides by -7 to isolate y
7/-7 = -1
-7y/-7 = y
-1 = y
our solution to the equation is y = -1. we can see if this is an answer by plugging it in and seeing if both sides are equal, but its not necessary. i will show the check anyway:
CHECK
5(2y - 1) = 3(y - 4) when y = -1
5(2(-1) - 1) = 3((-1)- 4)
5(-2 - 1) = 3( -1 - 4)
5(-3) = 3(-5)
-15 = -15
both sides check out so y = -1 is a solution to the equation